Exploring EFL learners' cognitive/emotional dissonance in content-based foreign language instruction: An ecological perspective. (June 2023) - Li, Dongying; Zhang, Lian
Abstract: Affective factors play an important role in language and cognitive development, but relevant research on students' cognitive/emotional experiences in foreign language instruction has been rather limited. The study adopts a case study method to investigate two EFL learners' reactions to cognitive/emotional dissonances in content-based foreign language instruction from an ecological perspective. Data include learners' retrospective interviews and reflections. Findings show that firstly dissonance not only reflects the challenges learners face but also triggers them to restructure their cognition and emotion that mutually transform one another in embodied actions. Secondly, learners' cognition, emotion and action constitute an amalgam in their attempts to resolve dissonances, through which personal traits (e.g., cognition, emotion and action) mutually interact with one another and with the contextual affordances (e.g., teacher, pedagogy and assessment). Finally, a curriculum that is relevant, meaningful and cognitively challenging inspires learners' resilience and engagement in learning while unlashing their developmental potentiality. Findings suggest the need to study cognitive/emotional dissonance in situated learning practices, to regard personal traits as dynamic and malleable and developing a foreign language curriculum that is personally meaningful and relevant.